Application of the QuEChERS method for the determination of organochlorine pesticide residues in Brazilian fruit pulps by GC-ECD. Issue 1 (2nd January 2017) - Paz, Mário; Correia-Sá, Luísa; Vidal, Carla B.; Becker, Helena; Longhinotti, Elisane; Domingues, Valentina F.; Delerue-Matos, Cristina
ABSTRACT: The Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) method was applied to the extraction of 14 organochlorine pesticides (OCPs) residues from commercial fruit pulps available in supermarkets in Fortaleza, Northeastern Brazil. The analyses were carried out by gas chromatography (GC), coupled to an electron-capture detector (ECD), and were confirmed by GC-tandem mass spectrometry (MS). The parameters of the analytical method, such as accuracy, precision, linear range, limits of detection and quantification, were determined for each pesticide. The results showed good linearity ( R 2 ≥ 0.9916) and the overall average recoveries were considered satisfactory obtaining values between 69 and 110%, RSD of 2–15 %, except for hexachlorobenzene (HCB) in açai, acerola and guava pulp samples. The OCPs were detected in guava (α–HCH; lindane) and soursop (α, β–HCH isomers) samples. The QuEChERS method and GC–ECD were successfully used to analyze OCPs in commercially available Brazilian fruit pulps and can be applied in routine analytical laboratories.